Investigation of the roles Librarians and Web Developers play in shaping the information architecture of the Namibia University of Science and Technology Library website - Coetzee, Justine (Library and Information Studies Centre (LISC), 2025)
A website's information architecture significantly influences its usability. Libraries increasingly relied on websites to provide access to resources and services, making effective information architecture crucial for user experience. Many library websites are poorly designed with weak navigation structures, which limits user engagement and makes it difficult to find information. As users increasingly rely on digital access, usability and clear navigation are essential for a positive experience. Despite the importance of library websites, their development often lacked proper planning, leading to complex and difficult-to-navigate structures. This study aimed to address these issues by examining the roles of librarians and web developers in shaping the Namibia University of Science and Technology (NUST) library website's information architecture. Therefore, this study investigated the principles of information architecture employed in the creation of the NUST library website. The objectives were to determine the roles librarians played in determining the website's information architecture, understand the librarians' perceptions of the library website's information architecture, and examine whether web developers considered information architecture principles during website development. It was guided by Morville and Rosenfeld's information architecture framework, which emphasises four key components: organisation, labelling, navigation, and search. This study employed a qualitative research approach, utilising methods such as interviews and document analysis to gather data from librarians and web developers involved in the creation and maintenance of the NUST library website. The study found that both librarians and web developers played essential roles in the creation of the NUST library website. Librarians focused on content accessibility, while developers handled technical structure and usability. These findings align with existing literature on information architecture in digital library environments. This research contributed to the library and information science field by shedding light on the collaborative roles of librarians and web developers in creating effective library website information architecture. The findings of the study advised best practices for designing user-centric library websites, improving user engagement, and enhancing the overall library experience.